Tannic acid, a promising anti-photoaging agent: Evidences of its antioxidant and anti-wrinkle potentials, and its ability to prevent photodamage and MMP-1 expression in L929 fibroblasts exposed to UVB - Daré, Regina G.; Nakamura, Celso V.; Ximenes, Valdecir F. [UNESP]; Lautenschlager, Sueli O.S. (Elsevier, 2020)
Chronic and unprotect UV exposure leads to skin oxidative stress, following accumulation of damaged cellular components and downstream activation of specific signaling pathways, culminating in premature skin aging (photoaging). In this concern, polyphenols have been proposed for the prevention of skin disorders UV-generated. In the present study, we compared gallic acid (GA) and tannic acid (TA) regarding their potentials in prevent photoaging, using cell-free assays. The most promising compound was further investigated for its photoprotection abilities in UVB-irradiated L929 fibroblasts. TA was more efficient in scavenging radicals DPPH•, superoxide anion, peroxyl, nitric oxide and peroxynitrite, and to reduce ferric ions. Although GA and TA exhibited similar inhibitory activity towards collagenase, TA was more potent in inhibit elastase. In addition, TA presented a broader UV absorption spectrum. Furthermore, TA treatment in UVB-irradiated cells attenuated redox imbalance, as observed by its ability to inhibit ROS production, NADPH oxidase activation and depletion of endogenous antioxidant defense system. Moreover, TA treatment prevented cellular photodamage and subsequently photoaging, by inhibiting lipid peroxidation, depolarization of mitochondrial transmembrane potential, DNA damage, and MMP-1 expression, a protein closely related to the structural degeneration of the dermis extracellular matrix. In conclusion, the results indicate the potential of TA in act as anti-photoaging agent, due to its potent antioxidant, anti-collagenase and anti-elastase activities, and UV-absorption effects, and its ability in prevent oxidative stress, oxidative damages and MMP-1 induction in UVB-irradiated L929 fibroblasts.
Keywords: Gallic acid; Oxidative stress; Photoaging; Tannic acid; UVB